Strategi Komunikasi Korporat AXA Mandiri Dalam Menjaga Reputasi - Dirgantoro, Ganet; Patrianti, Tria (Universitas Prof. Dr. Moestopo (Beragama), 2025)
AXA Mandiri as a life insurance company certainly has an obligation to maintain its reputation so that public trust is always well managed. Usually for companies in the financial sector, trust is an important condition that must always be upheld because it concerns funds entrusted in the long term. On the other hand, the challenges faced by life insurance companies in the future are also getting heavier due to the rapid exposure to the news, plus the awareness of insurance is still low. The position of AXA Mandiri, which is ranked fourth in life insurance companies in terms of capital and premium acquisition in 2024, certainly requires a measurable and well-managed corporate communication strategy. The research aims to analyze corporate communication strategies in maintaining reputation. The research method uses a qualitative case study approach using the Chief Communication Officer as a key informant referring to the theory of corporate communication, reputation, and image. The results of the study show that the strategy is implemented through media monitoring to ensure that corporate communication is well managed, the response is carried out at that time also involves third parties, appoints spokespersons, and clarifies by involving the mass media.